PERNIKAHAN DINI DALAM PERSPEKTIF HUKUM DI INDONESIA: TANTANGAN DAN PENCEGAHANNYA - Putri, Nadita Felisa (Legal Studies Journal, 2025)
Early marriage is still a phenomenon that is difficult to eliminate in Indonesia even though there are stricter regulations. This study aims to analyze the challenges faced in preventing early marriage and its impact on individuals and society. With a normative legal approach, this study examines the applicable legal policies and examines the challenges of their implementation. The results of the study indicate that although Law Number 16 of 2019 has increased the age limit for marriage to 19 years, there are still legal loopholes in the form of dispensations that allow early marriage to continue to occur. In addition, social, economic, cultural factors, and lack of public awareness are still the main obstacles in preventing early marriage. Government efforts such as socialization, data collection, and supervision of the KUA still need to be strengthened with stricter sanctions and a community-based approach so that prevention is more effective. Therefore, a more comprehensive strategy is needed that not only emphasizes the legal aspect, but also involves public education and improving economic welfare to reduce the number of early marriages in Indonesia.